A Generic User-Defined Modeling Method in PSS/E and Its Application in an MMC-HVDC System - Zhu, Lin; Wu, Zhigang; Chen, Da; Chen, Yuchuan; Xing, Chao; Li, Qing (Frontiers in Energy Research, 2022)
This paper studies the user-defined modeling (UDM) method in PSS/E and applies it to a modular multilevel converter high-voltage direct current (MMC-HVDC) system. First, the mechanism of PSS/E UDM is discussed, including the requirements of the model call, storage space allocation, and flows of dynamic simulation. Then, a generic UDM method applicable to various objects is proposed in PSS/E, considering both the internal structures of models and their interfaces with the PSS/E main program. Next, the design of multiple time scales of UDM is presented for hybrid step size simulation. Accordingly, a user-defined MMC-HVDC system model is built in PSS/E considering the converter, DC-line, control system, and system interface. Finally, the model is compared with a PSCAD electromagnetic transient MMC-HVDC model in a modified two-area-four-generator system. The simulation results demonstrate the proposed UDM method.